2020
DOI: 10.3390/microorganisms8111792
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis B Virus Markers in Patients with Autoimmune Inflammatory Rheumatic Diseases in Italy

Abstract: Chronic hepatitis B virus (HBV) infection may be reactivated by immunosuppressive drugs in patients with autoimmune inflammatory rheumatic diseases. This study evaluates HBV serum markers’ prevalence in rheumatic outpatients belonging to Spondyloarthritis, Chronic Arthritis and Connective Tissue Disease diagnostic groups in Italy. The study enrolled 302 subjects, sex ratio (M/F) 0.6, mean age ± standard deviation 57 ± 15 years, 167 (55%) of whom were candidates for immunosuppressive therapy. The Spondyloarthri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
(58 reference statements)
1
4
1
4
Order By: Relevance
“…Moreover, the time course of monitoring showed a long delay (16 weeks) between the first mild increase in ALT level and the identification of HBsAg seroreversion [23]. The results of our study are in line with our previous data [9] showing both no HBV reactivation, a prevalence of anti-HBc positivity of 14.1%, which is higher than that observed in most Western countries (about 7%) [24] but is similar to that observed by other authors in Italian patients with rheumatic disease [25]. Moreover, we have now also shown that the prHBV status is not associated with RTX treatment discontinuation.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the time course of monitoring showed a long delay (16 weeks) between the first mild increase in ALT level and the identification of HBsAg seroreversion [23]. The results of our study are in line with our previous data [9] showing both no HBV reactivation, a prevalence of anti-HBc positivity of 14.1%, which is higher than that observed in most Western countries (about 7%) [24] but is similar to that observed by other authors in Italian patients with rheumatic disease [25]. Moreover, we have now also shown that the prHBV status is not associated with RTX treatment discontinuation.…”
Section: Discussionsupporting
confidence: 91%
“…In Our study, we included a full HBV virology panel prior to the commencement of immunosuppressive therapy and during the follow-up period. It should be mentioned that we noticed 43.5 percent of our study cohort were adequately previously immunized with protective antibody titers > 10 IU/L with a higher incidence compared to the recent study done in Italy by Canzoni M et al (2020), in which only 3% were immunized prior to commencement of immunosuppressives, and this may reflect the adequacy of childhood vaccination.…”
Section: Figure 3 Group Classification and Interventions During Follo...contrasting
confidence: 52%
“…Moreover, the coexistence may also occur in the presence of hyperimmune function. As HBV is a common comorbidity among rheumatic patients, HBV infection may reactivate in patients with autoimmune inflammatory rheumatic diseases when they take immunosuppressive drugs or undergo biological therapies 99 , 100 . The HBV infection needs surveillance, and markers like HBsAg and anti-HBs need to be detected before and after the treatment of co-infected diseases.…”
Section: Clinical Characteristics and Significances In Coexistencementioning
confidence: 99%